A Thematic and Chronological Analysis of the Reception of Ananias and Sapphira (Acts 5:1â??11) in the First Five Centuries CE. Issue 2 (4th May 2017) - van der Bergh, Ronald H.
ABSTRACT: This article investigates the reception of Acts 5:1–11 (the narrative of Ananias and Sapphira) in the writings of the early church. The article categorises how authors up to the end of the fifth century CE made use of this pericope in their reasoning. Chronologically, the analysis shows how the reception of this pericope went from a discussion of sin and punishment to one of the prime proof texts for demonstrating the divinity of the Holy Spirit.